STRATEGI BERBAHASA CALON KEPALA DAERAH PADAWACANA KAMPANYE PILKADA JAWA BARAT 2018 - Sudaryanto Sudaryanto; Dedi Wijayanti (Jurnal Membaca Bahasa dan Sastra Indonesia, 2019)
Regional head candidates, especially governors and deputy governors of West Java province for the period 2018—2023, have unique and interesting Indonesian, regional (Sundanese), and foreign (English) language strategies to study. Through their campaign props, they tried to attract voters to vote for him. The data in the form of campaign discourse of the governor and deputy governor candidates of West Java province was collected through an observation method with reading and recording techniques. Then the data is analyzed by matching methods through referential equivalent techniques, orthographic equivalent techniques, and phonetical equivalent techniques. The results of this study indicate that the candidates for regional head use various strategies in Indonesian, regional (Sundanese), and foreign (English) languages, such as acronyms, abbreviations, jargon, honorifics, self-names, brief biodata, bearer party names, and social media names.